Effects of sexual harassment on learning experience among teenager girl students at Lalitpur District - Gyawali, Kalpana; Maharjan, Ram Krishna (Interdisciplinary Research in Education, 2022)
The study aimed to analyze the effects of sexual harassment on the learning experience on the girl students in Nepal. Concurrent mixed-method was used for study among 371 girl students who were studying at community and institutional schools of the Lalitpur district, Nepal . The sample size for the quantitative study has been calculated at a 95% confidence level with a 5 confidence interval. Five focus group discussions (FGD) and three in-depth interviews (IDI) were conducted to collect qualitative data. IBM SPSS 20 was used for quantitative data analysis and a thematic approach was used for qualitative data analysis. Learning motivation, interaction with a teacher, self-learning, and class discussion activities among girl students were found significantly affected by sexual harassment and sexual harassment was found as one of the causal factors behind poor learning activitys and achievement on the girl students in Lalitpur, Nepal.